Fetal exposures and perinatal influences on the stool microbiota of premature infants - Chernikova, Diana A. (J Matern Fetal Neonatal Med, 2015)
OBJECTIVE: To test the hypothesis that maternal complications significantly affect gut colonization patterns in very low birth weight infants. METHODS: 49 serial stool samples were obtained weekly from 9 extremely premature infants enrolled in a prospective longitudinal study. Sequencing of the bacterial 16S rRNA gene from stool samples was performed to approximate the intestinal microbiome. Linear mixed effects models were used to evaluate relationships between perinatal complications and intestinal microbiome development. RESULTS: Subjects with prenatal exposure to a non-sterile intrauterine environment, i.e. PPPROM and chorioamnionitis exposure, were found to have a relatively higher abundance of potentially pathogenic bacteria in the stool across all time points compared to subjects without those exposures, irrespective of exposure to postnatal antibiotics. Compared with those delivered by Caesarean section, vaginally delivered subjects were found to have significantly lower diversity of stool microbiota across all time points, with lower abundance of many genera, most in the family Enterobacteriaceae. CONCLUSIONS: We identified persistently increased potential pathogen abundance in the developing stool microbiota of subjects exposed to a non-sterile uterine environment. Maternal complications appear to significantly influence the diversity and bacterial composition of the stool microbiota of premature infants, with findings persisting over time.